Active Braking Control Systems Design for Vehicles - Savaresi, Sergio M.; Tanelli, Mara (Advances in Industrial Control,, 2010)
Active Braking Control Systems Design for Vehicles focuses on two main brake system technologies: hydraulically-activated brakes with on-off dynamics and electromechanical brakes, tailored to brake-by-wire control. The physical differences of such actuators enjoin the use of different control schemes so as to be able fully to exploit their characteristics. The design of such control systems forms the core of this monograph. The authors show how these different control approaches are complementary, each having specific peculiarities in terms of either performance or of the structural properties of the closed-loop system. They also consider other problems closely related to the design of braking control systems, namely: • longitudinal wheel slip estimation and its relationship with braking control system design; • tyre-road friction estimation; • direct estimation of tyre-road contact forces via in-tyre sensors, with the aim of providing a comprehensive treatment of active vehicle braking control from a wider perspective linked to both advanced academic research and industrial reality. The high degree of cooperation with the automotive industry in the research which generated much of the work presented here, coupled with survey sections in which problems and methodologies are introduced in a historical and tutorial framework, makes this book accessible from three standpoints: a methodological one for academic research; an application-oriented one for automotive engineers and practitioners; and a source of study and tuition for graduate students interested in vehicle control systems.